A Study on the Effectiveness of the Advertising Techniques Used in the Personal Care Segment of Women Consumers - Kavitha, G. (Indian Journal of Marketing, 2006)
Advertising of late, has become a huge industry in India and there is no escaping from it. Today, just advertising a product is not enough. A lot of research needs to be done on the unique selling proposition of the product, the target audience, consumer's demographics, consumer behaviour and many more. The advertisers need to analyse the various techniques that can be used for advertising and choose the most effective of the lot. A technique, which is successful for one product category, may not necessarily work well for an other category or even other brand.